Overview of the Prevalence and Contributing Factors for Occupational Noise-Induced Hearing Loss (NIHL) in Malaysia - Abdul Razak, Nur Faiza; Mohd Aris, Mohd Shukri (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: This manuscript aims to provide a synopsis of the current situation surrounding noise exposure at work and the risk of noise-induced hearing loss (NIHL) in Malaysia. NIHL is an occupational illness that affects most many people and can be prevented in many countries in the world. The production and agriculture businesses and the extraction of natural resources and urban traffic all contribute to ambient noise levels. Working in a noisy environment is the main occupational risk factor for adult-onset hearing loss. In this study, we investigate the prevalence of NIHL across different industries, as well as research publication trends on NIHL. MATERIAL AND METHODS: Conducted thorough several online databases, like Science Direct, Web of Science, and Google Scholar, for related research that had already been published. The review phases were carried out according to the recommendations laid out by the preferred reporting items for systematic reviews. A set of criteria was developed for selecting relevant studies. RESULTS: The prevalence of NIHL among workers in Malaysia, varies across different industries and has been reported to range from 5.0% to 82.6%. NIHL has multiple contributing factors, including noise intensity, long-term exposure to daily noise, hearing protection devices and age. A review of these studies found varying percentages of individuals affected by each contributing factor. CONCLUSION: Occupational NIHL is a preventable health risk for workers across industries. Employers must adopt engineering and administrative controls (education and training) and provide personal hearing protectors to protect workers from noise.